CRISRP/Cas9-Mediated Targeted Mutagenesis of Tomato Polygalacturonase Gene (SlPG) Delays Fruit Softening - Nie, Hongmei; Shi, Yu; Geng, Xueqing; Xing, Guoming (Frontiers in Plant Science, 2022)
Polygalacturonase (PG) gene has been documented as a key candidate for the improvement of fruit firmness, which is a target trait for tomato production, because it facilitates transportation and storage. To reduce the expression of PG gene, most of the elite commercial tomato varieties were obtained by RNA interference technology. However, this approach of producing commercialized tomatoes by integrating of exogenous gene is controversial. In this work, CRISPR/Cas9 technology was used to induce the targeted mutagenesis of SlPG gene to delay the softening of tomato fruit. Result showed that SlPG gene was frameshift mutated by 4 bp deletion, 10 bp deletion and 1 bp insertion, which generated premature translation termination codons. Compared with wild-type (WT), homozygous T1-generation tomato plants exhibited late fruit softening under natural conditions. Consistent with this phenomenon, the firmness value of WT fruit was lower in slpg mutant fruit, and the physiological loss of water was higher. Collectively, these data demonstrate that the mutation of SlPG gene delays tomato fruit softening. More importantly, 8 out of 20 transgene-free tomato plants, which were homozygous for null alleles of SlPG, were separated in the T3-generation of line slpgT2-#2. These transgene-free slpg may provide materials for more in-depth research of SlPG functions and the molecular mechanism of fruit softening in tomato.